Embattled nation : Canada's wartime election of 1917 - Dutil, Patrice A., 1960-; MacKenzie, David, 1953- (Toronto : Dundurn, 2017)
Embattled Nation explores Canada's tense wartime election of 1917. Amidst the drama of the First World War, Canada's most divisive election ever raised pivotal questions about Canada's place in the war and the world. This book examines the issues, people, and events behind one of the most important elections in Canada's history.
Preface -- Acknowledgements -- The Conundrum: Robert Borden, War, and the Call for an Election -- The Response of French Canada: Henri Bourassa, Schools, and Nationalities -- The Issue: Conscription -- The Liberals in Opposition: Wilfrid Laurier's Leadership Tested -- Creating Divisions, Choosing Sides: The Great Gerrymander -- Framing the Campaign -- The Campaign: French Canada -- The Campaign: English Canada -- The Results -- The Aftermath: Union without Unity -- Conclusion.
Includes bibliographical references and index.
Text in English.
eBooks on EBSCOhost
Keywords: Borden, Robert Laird, -- Sir, -- 1854-1937.; Laurier, Wilfrid, -- Sir, -- 1841-1919.; Canada. -- Parliament -- Elections, 1917.; Borden, Robert Laird, -- Sir, -- 1854-1937; Laurier, Wilfrid, -- Sir, -- 1841-1919; Canada. -- Parliament; Canada -- Politics and government -- 1911-1921.; HISTORY -- Canada -- Post-Confederation (1867- ); 1917